Ischaemic Stroke as A Presenting Feature of Polycythemia RubraVera - A Case Report (Anwer Khan Modern Medical College Journal, 2013)
Stroke secondary to polycythemia rubra vera (PRV) is very uncommon. A 55 years old man presented to us with ischaemic stroke, imaging revealed one recent and multiple previous Lacunar infarcts. Evaluation for underlying cause proved him as a case of PRV. Effective treatment of PRV can prevent the further recurrence of Ischaemic stroke DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13686 AKMMC J 2013: 4(1): 45-47